2022
DOI: 10.3390/jcm11226790
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Functional Cortical Plasticity in Children with Cerebral Palsy Associated to Robotic-Assisted Gait Training: An fNIRS Study

Abstract: Cerebral palsy (CP) is a non-progressive neurologic condition that causes gait limitations, spasticity, and impaired balance and coordination. Robotic-assisted gait training (RAGT) has become a common rehabilitation tool employed to improve the gait pattern of people with neurological impairments. However, few studies have demonstrated the effectiveness of RAGT in children with CP and its neurological effects through portable neuroimaging techniques, such as functional near-infrared spectroscopy (fNIRS). The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 39 publications
(46 reference statements)
2
17
0
Order By: Relevance
“…The novel observation of decreased ΔHbO in children with CP compared to controls is consistent with previous work reporting decreased PFC hemodynamic activity in children with spastic CP during a robot‐assisted walking task (Perpetuini et al, 2022). While another study reported increased PFC hemodynamic activity in children with CP (Surkar et al, 2018), the task involved cognitive shape‐matching using the upper extremities and was performed in a seated position.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The novel observation of decreased ΔHbO in children with CP compared to controls is consistent with previous work reporting decreased PFC hemodynamic activity in children with spastic CP during a robot‐assisted walking task (Perpetuini et al, 2022). While another study reported increased PFC hemodynamic activity in children with CP (Surkar et al, 2018), the task involved cognitive shape‐matching using the upper extremities and was performed in a seated position.…”
Section: Discussionsupporting
confidence: 90%
“…Studies in other neurologically impaired populations reported increased PFC activation during gait and postural control tasks in individuals with Parkinson's disease and post‐stroke (Gramigna et al, 2017; Stuart et al, 2018). The sole study assessing PFC hemodynamic activity during a functional mobility task in children with CP reported decreased PFC activity during a robot‐assisted walking task, with increased PFC activity observed post‐training associated with improvements in gait characteristics (Perpetuini et al, 2022). These observations support the potential of PFC hemodynamic activity levels to serve as possible biomarkers of functional recovery following brain injury (Stinear, 2017; Surkar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, resting state and task-based paradigms have been used to evaluate activation differences among young children who are and are not high risk for ASD, with the clinical goal of identifying early quantitative biomarkers ( Conti et al, 2022 ). Further, fNIRS has been used to evaluate differences in brain activation during physical movement between children with and without cerebral palsy (CP; Sukal-Moulton et al, 2014 ) and to explore activation changes during treatment with the goal of intervention individualization ( Cao et al, 2015 ; Perpetuini et al, 2022 ). Although fNIRS may still be considered a novel neuroimaging tool in comparison to other modalities (e.g., electroencephalogram, fMRI), outcomes of fNIRS studies with ADHD participants have demonstrated convergence with fMRI findings, supporting the clinical usefulness and reliability of fNIRS as a tool in ADHD research ( Gossé et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, RAGT facilitates patients' alternate step movements, which would reproduce patterns of physiological muscle activation [101] and increase motor learning as a result of a task-specific repetitive approach [102]. A recent study, published in November 2022 by Perpetuini and colleagues, showed that RAGT produces modifications in the motor and pre-frontal brain cortex, improving motor control and attention during RAGT in children with CP [103], showing that neuroplasticity is essential in the recovery of these patients. For motor control improvements, RAGT produced bilateral changes in cortical areas BA 1, 6, 9, 11 and 46, which are involved in motor coordination and complex movements (BA 6 and 9), proprioceptive control (BA 1), spatial memory (BA 9) and in attention, self-control and working memory (BA 9 and 46).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, RAGT requires active and total participation of children in the therapy and can be used in combination with other activities of daily living that need standing balance training. Moreover, active participation involves attention and engagement in the therapy, which would involve an increase of activity in the pre-frontal cortex [103]. RAGT seems to improve cardiopulmonary function, allowing patients to perform activities for more time without experiencing fatigue or tiredness [104].…”
Section: Discussionmentioning
confidence: 99%